Effect of Storage Conditions on Wheat Seed Quality and Germination and Microbial Activity - Kamil, Fatima Abdullah (American Journal of Botany and Bioengineering, 2025)
The reason for our study of the wheat crop is because it is of great importance due to the important strategic position this crop represents, as well as its social, economic and security significance at the national level in general and the individual level in particular. Therefore, it is necessary to move towards developing wheat storage methods to achieve better results than those obtained by traditional methods. Obtain wheat seed samples from a variety of sources, including commercial stores, research centers, and local farms. Use visual analysis and initial moisture content tests to categorize samples based on their quality and type. Prepare three temperature levels: low (10-15°C), moderate (20-25°C), and high (30-35°C). Adjust humidity levels to low (<10%), moderate (10-20%), and high (>20%). Utilize three varieties of packaging: the first was using tightly sealed plastic, the second was using paper bags, and the third was using loose paper bags. You can store seeds for 3, 6, and 12 months under the specified conditions. The effect of temperature on the germination rate of wheat plants, where there are three levels of temperature. The first was the low temperatures used in storage, ranging between 10-15°C, while the other was between 20-25°C. The third level of temperature was high, more than 35°C. After taking a group of seeds randomly and growing them, there was a large and clear difference in the germination rate, which was higher in the seeds stored at low temperatures, as they gave a high germination rate of up to 95%. As for the seeds stored at medium temperatures, they gave a germination rate of up to 70%, while those stored at high temperatures had a germination rate of 40%. The reason may be attributed to the effect of temperature on inhibiting some enzymes necessary for the work of enzymes.